Spring reproductive and vegetative phenology of olive (Olea europaea L.) cultivars at different air temperatures along a latitudinal-altitudinal gradient in Argentina - Hamze, Leila Mariam; Trentacoste, Eduardo Rafael; Searles, Peter Stoughton; Rousseaux, María Cecilia (Elsevier, 2022)
Detailed spring phenology studies are scarce in olive trees growing in non-Mediterranean climates despite crop expansion into new regions in the last few decades. Additionally, the vegetative phenology of olive trees has been little examined under any climate conditions. Thus, the aims of this study were to: (i) evaluate the timing of spring reproductive and vegetative phenological stages and their overlap for several olive cultivars growing under different air temperatures along a latitudinal gradient (29°–33° S) that included a range of altitudes (450–1,250 m asl) in western Argentina; and (ii) assess the potential relationships between the length (i.e., days) of some phenological phases and air temperature. All observations were performed during two growing seasons (2018–2019, 2019–2020). The temperature difference across the latitudinal-altitudinal gradient during the winter and early spring periods was between 4.2 and 6.0 °C. The separation of the first leaves (BBCH 11) most often occurred after inflorescence bud opening (BBCH 53) at warmer low latitude locations, but before BBCH 53 at cooler high latitude sites. A difference of 26 days in full flowering was found between extreme locations when considering both seasons. The variability of the reproductive stage dates was explained mostly by environmentally-related factors including location (71.7–95.2%) and season (0–18.1%) rather than by cultivar (2.8–6.6%). Nevertheless, cultivar responses did appear to depend on the climate conditions at different locations and growing seasons. The length of the inflorescence emergence phase (BBCH 53–60) decreased by 4.3 days/ °C as the mean air temperature during the phase increased. In contrast, the flowering phase length (BBCH 60–69) decreased with increasing mean air temperature during the phase up to 23 ºC, but increased above that temperature. These results should be useful for better timing of management practices and the development of phenological models that include non-Mediterranean environments.